The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0088992
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Survey of Genetic Instability by Transposition in Drosophila Hybrids

Abstract: Hybridization between species is a genomic instability factor involved in increasing mutation rate and new chromosomal rearrangements. Evidence of a relationship between interspecific hybridization and transposable element mobilization has been reported in different organisms, but most studies are usually performed with particular TEs and do not discuss the real effect of hybridization on the whole genome. We have therefore studied whole genome instability of Drosophila interspecific hybrids, looking for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 55 publications
4
46
2
Order By: Relevance
“…In another Drosophila model, with hybrids between D. buzzatti and D. koepferae , Vela et al . (2014) showed, in a genome-wide manner, massive rearrangements in the F1 hybrids24. In both systems, a wide variety of TEs were responsible for most of the genomic instability in the hybrids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In another Drosophila model, with hybrids between D. buzzatti and D. koepferae , Vela et al . (2014) showed, in a genome-wide manner, massive rearrangements in the F1 hybrids24. In both systems, a wide variety of TEs were responsible for most of the genomic instability in the hybrids.…”
Section: Discussionmentioning
confidence: 95%
“…In artificially interspecific hybrids between D. melanogaster and D. simulans , TEs are derepressed due to adaptive divergence in the piRNA genes of both species rather than differences in TE contents23. Other studies with crosses between D. buzzatti and D. koepferae have shown that 70% of the genomic rearrangements observed in hybrids was due to TE insertions24.…”
mentioning
confidence: 99%
“…Previous work in our laboratory showed that new TE insertions occur in hybrids between the species Drosophila buzzatii and Drosophila koepferae (buzzatii complex, repleta group) [15,22,23], which is likely at the origin of a genome expansion in hybrid females [24]. These TE bursts have been associated with abnormal TE expression patterns, first of the retrotransposons Osvaldo and Helena [25,26] and then in a global transcriptomic study including the whole-genome TEs [27].…”
Section: Introductionmentioning
confidence: 97%
“…The stressors include both biotic factors, such as inbreeding [88, 89] and interspecific hybridization [9092], and abiotic factors. Among environmental stressors is the physical factor of heat shock which has been demonstrated to increase transposition rates of a variety of elements by one or two orders of magnitude in diverse organisms from yeast to flies [8183, 93, 94].…”
Section: Introductionmentioning
confidence: 99%